Shared decision making in implantable cardioverter-defibrillator patients. (25th November 2020) - Yilmaz, D; Egorova, A; Lensvelt, L.M.H; Van Erven, L
Abstract: Background: Implantable cardioverter-defibrillators (ICD) are effective in the prevention of sudden cardiac death and treating life-threatening arrhythmias. As the number of older patients increases, the number of implanted devices does as well. Evidence for current guidelines is mostly derived from trials conducted decades ago, in selected patient groups. Communicating the risks and benefits of an ICD to patients can be challenging. Shared decision making with the use of a decision aid has proven to result in more active patient participation and improved outcomes in several fields. Purpose: The aim of our study is to evaluate the effect of an ICD specific decision aid in clinical practice. Methods: We developed an evidence based decision aid according to the Delphi method. The decision aid was tested in 6 Dutch centres within a stepped wedge clustered randomized trial. We compared pre-procedural counselling with and without the use of a decision aid. Level of shared decision making was measured with the SDM-Q-9 in patients and SDM-Q-doc in caregivers. Additionally, we measured decisional conflict in patients with the decisional conflict scale questionnaire (DCS). This includes a subscore on how informed patients deemed to be. We included a set of 4 knowledge questions in our questionnaire. Differences between scoresbetween groups were analysed using the Mann-Whitney U test or One-way ANOVA. For categorical variables, we used the Chi-square test or Fishers Exact test accordingly. Results: In total, we retrieved questionnaires from 234 caregivers and 150 patients. The majority of the patients were male (75%) and the mean age was 70±9 years. Levels of shared decision making were marked high in all groups. With the use of a decision aid, caregivers experienced significantly more shared decision making (median 78 (IQR 62–84) versus 81 (IQR 71–87) in the decision aid group (p=0.002)). Patients reported low levels of decisional conflict in both groups. There were also no differences for the subscales of the DCS (median 17 (IQR 6–25) in the control group vs 14 (IQR 5–23) in the decision aid group (p>0.05)). Patients reported to be very well informed (DCS subscale score of 0 in the control group vs 8 with a decision aid, p<0.05), although they answered the knowledge quiz poorly in both settings, with only 1 patient (0.067%) answering all the four question correctly (p<0.05). Conclusions: Patients and caregivers report high levels of shared decision making. This is likely due to a bias associated with the study design, in which all participating centres were required to conduct elaborate pre-implantation counselling with patients as standard care, which is different from current clinical practice. Despite the implications of an ICD procedure, there was no decisional conflict and patients report to be well informed. This is in spite of low scores on the knowledge quiz. This illustrates the phenomenon of the unconsciously uninformed patient. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Federation of Medical Specialists (SKMS), Utrecht, The Netherlands